Do Tourism-Related Sectors Drive Most of the Economy in Toba Regency? A RAS-based Regional Input-Output Analysis - Susanti, Hera; Revindo, Mohamad Dian; Iskandar, Sulistiadi Dono; Nusantoro, Nalendro; Sabrina, Syahda (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah, 2025)
Research Originality: This study constructs the first regional Input–Output (RIO) table for Toba Regency in 2023, utilizing the iterative RAS technique to adapt provincial coefficients to local macroeconomic data. Research Objectives: To estimate sectoral interlinkages, multiplier effects, and labor intensity for Toba Regency, and to identify strategic sectors that can drive regional economic growth and inform evidence-based policymaking. Research Methods: The 2016 North Sumatra I–O table was regionalized into a 22-sector Toba Regency table through RAS, with row and column sums adjusted to match Toba Regency GRDP by industry and expenditure. The resulting table was analyzed to calculate backward and forward linkages, output multipliers, and labor intensity. Empirical Results: The local economy is primarily driven by paper manufacturing, agriculture, and construction, while the tourism sector contributes only 6.2 percent of output and exhibits weak forward linkages. This finding suggests limited integration of tourism-related activities into the local supply chain. Electricity, business services, and agriculture emerge as growth drivers, while wage disparities persist in low-productivity service sectors. Implications: The approach can guide other subnational governments in producing localized Input–Output (I–O) tables, thereby enhancing evidence-based policymaking. JEL Classification: D57, R15, R58 How to Cite:Susanti, H., Revindo, M.D., Iskandar, S.D., Nusantoro, N., & Sabrina, S. (2025). Do Tourism-Related Sectors Drive Most of the Economy in Toba Regency? A RAS-based Regional Input-Output Analysis. Signifikan: Jurnal Ilmu Ekonomi, 14(2), 521-536. https://doi.org/10.15408/sjie.v14i2.46490.